Efficient multicasting and broadcasting in layer 2 provider backbone networks. - Elangovan, Anush
Ethernet has grown from its roots in LANs to contend in previously unchartered territory of MANs and WANs. A slew of projects underway in the IEEE 802 standards bodies plan to groom Ethernet with carrier grade features like high availability, fault management, and resiliency thus far found only in other circuit-switched technologies. These include, among others, IEEE 802.1ag (connectivity fault management), IEEE 802.1ad (provider bridges), and IEEE 802.1ah (provider backbone bridges). IEEE 802.1ah addresses the service and MAC address scalability of provider backbone bridges. Since Ethernet has been architected and designed for a shared medium, it inherently handles broadcast and multicast traffic very efficiently, unlike layer 3 technologies, where multicasting and broadcasting rely on using multiple point-to-point connections. With IEEE 802.1ah, Ethernet would be able to provide millions of service instances in a provider backbone network. While flooding of frames in a LAN may provide for good multicasting, flooding of data in a MAN or WAN could mean huge bandwidth wastages, especially when the remote peers are geographically distant, and the traffic is not necessarily destined to any of its local ports of the peers. In this article we explore technologies to Address efficient multicasting in provider backbone networks. We also consider extending this technology to address unknown unicast floods and efficient proxy of customer multicast frames.
Keywords: Ethernet; IEEE 802 standards; broadcast traffic; broadcasting; layer 2 provider backbone networks; multicasting